Wnt/β-catenin signaling in adipogenesis and metabolism - Prestwich, Tyler C. (2007)
Adipocyte differentiation consists of a complex series of events in which scores of cellular and extracellular factors interact to transform a fibroblast-like preadipocyte into a mature, lipid-filled adipocyte. Many of the pathways influencing this process have been identified using well-characterized preadipocyte culture systems and have subsequently been confirmed in animal models. Research conducted over the last decade has established the Wnt/β-catenin signaling pathway as an important regulator of adipocyte differentiation. While initial reports implicated activators of Wnt/β-catenin signaling as potent inhibitors of adipogenesis, recent investigations of mesenchymal cell fate, obesity, and type 2 diabetes highlight significant additional roles for Wnt signaling in metabolism and adipocyte biology.